Parental Obesity and Autism Spectrum Disorder - J Gordon Millichap; John J Millichap (Pediatric Neurology Briefs Publishers, 2014)
Investigators from Oslo, Norway and other centers studied the associations among maternal prepregnancy BMI, paternal BMI, and the risk of autism spectrum disorder (ASD) in children.